Optimal Allocation of Decision-Making Authority and the Provision of Incentives under Uncertainty - Anja Schöttner; Anna Rohlfing-Bastian (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Incentives for managers are often provided by offering them performance-based compensation schemes. The efficiency of such monetary compensations, however, depends on several factors, among them the quality of the employed performance measures, the information available for contracting purposes, and the allocation of decision-making authority which translates into either more centralized or more decentralized organizational structures. This article investigates a firm's decision whether to delegate or retain the authority to decide on a specific job design in a moral hazard environment with asymmetric information on effort costs. It provides conditions under which decentralization is the preferred organizational form. Moreover, it derives the result that the relation between incentives and the delegation of decision-making authority is not univocal, but depends on the quality of the employed performance measure. In this regard, it contributes to explaining the mixed empirical evidence on the relation between incentives and decision-rights.
Keywords: M52; M55; M21; 330